"Gestión de procesos y su incidencia en la producción y rentabilidad de la hacienda bananera Vanessa del cantón Valencia año 2010-2012 Plan de gestión por procesos". - Morante Anchundia, Daniel Assad (2013)
Bananas are the fourth most important crop in the world, is considered an export commodity and source of employment and income in many developing countries. It is believed that it was the Arabs who initially brought banana plants to Spain and then was brought to America by the Dominicans. Plantains and bananas are one of the main products of the daily diet for about 400 million people. Although it ranks fourth after rice, maize and wheat among food products worldwide, its production is threatened by many diseases and pest problems. Banana cultivation worldwide in terms of cultivated area is estimated at 5'029 30'471 hectares producing 997 870 tons / year, of which 73% are concentrated in countries in Africa, 3% in Asia and the 24% in Latin America and Caribbean (530 7'008 ton), where Colombia, Costa Rica, Ecuador, Panama, Peru and Venezuela are the main producers (FAO 2002). Its consumption is predominantly fresh and immediate marketing, presenting special marketing features common to other perishables that make up a complex system of production and distribution, in the process involved the producers and intermediaries, who are in charge of distributing the product to the final consumer in the domestic and foreign markets. Develops research considering the process management system to improve production and profitability through Vanessa Finance Process Management Plan under the guidance of the methodology. The proposed research topic, in the first part contains an analysis of the weaknesses of the organization to improve the competitiveness of the company, we proceeded to identify the processes that provide a competitive advantage by relating them to the value perceived by customers, we will analyze the Control system in each of the processes.In the second part performance indicators were established processes andfinally designed a Process Management Plan for the property bananaproducer Vanessa Valencia Canton, year 2010-2012.